Review on COVID-19: Rise of SARS-CoV-2 Pandemic Outbreak - Vidhan Chand Bala; Punet Kumar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Initially recognized of COVID-19 within the world in 2019, the World Health Organization situational report from May 22nd, 2020, globally, there is a complete of 5,204,508 confirmed cases, with 212 countries being affected by the novel coronavirus. 2019 novel coronavirus (SARS-CoV-2) is that the seventh member of the family of coronaviruses is enveloped viruses with a positive sense, single-stranded RNA genome. The SARS-CoV-2 may be a β-CoV of group 2B there is 70% comparability in genetic sequence to SARS-CoV. The source of the new coronavirus infection has been resolved as bats. With whole-genome sequences of SARS-CoV-2 is 96% comparatively at the whole-genome level to a bat coronavirus. Mechanisms of transmission are concluded to incorporate contact, droplet, and possibly airborne under certain circumstances supported ancient experiences associated with SARS-CoV outbreaks. Although antiretroviral therapy is being widely used everywhere the globe for such patents, effects at finding a SARS-CoV vaccine haven’t succeeded so far.